Concept and types of aviation under the law of Russia and Ukraine - Аксаментов, Олег Ігорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The short review of operating sources of an air law of Russia and Ukraine is provided in article. It is described the public relations which are subject to regulation by norms of the air legislation. Subjects of legal regulation of an air law of Russia and Ukraine are compared.